2013
DOI: 10.1016/j.neuroimage.2013.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Dominant frequencies of resting human brain activity as measured by the electrocorticogram

Abstract: The brain’s spontaneous, intrinsic activity is increasingly being shown to reveal brain function, delineate large scale brain networks, and diagnose brain disorders. One of the most studied and clinically utilized types of intrinsic brain activity are oscillations in the electrocorticogram (ECoG), a relatively localized measure of cortical synaptic activity. Here we objectively characterize the types of ECoG oscillations commonly observed over particular cortical areas when an individual is awake and immobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
136
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(151 citation statements)
references
References 62 publications
(124 reference statements)
13
136
1
1
Order By: Relevance
“…All patients were confronted with stressogenic experiences, in concordance with previous studies suggesting stress as an important risk factor for the development of PSs. Analysis of intracranial recordings of patients with epilepsy in the resting state showed that a cluster at the theta range characterizes resting-state activity at the 'default-mode network' in which the posterior parietal cortex plays a key role [12]. This is in concordance with previous resting-state fMRI findings showing stronger connectivity values within Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All patients were confronted with stressogenic experiences, in concordance with previous studies suggesting stress as an important risk factor for the development of PSs. Analysis of intracranial recordings of patients with epilepsy in the resting state showed that a cluster at the theta range characterizes resting-state activity at the 'default-mode network' in which the posterior parietal cortex plays a key role [12]. This is in concordance with previous resting-state fMRI findings showing stronger connectivity values within Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The posterior parietal cortex is related to self-processing [15] and is implicated in autobiographical thinking about past and future events [16]. We speculate that PSs, reflecting conflicts related to one's past and current self-referenced dilemmas, are related to a dysfunction of the default-mode network [12] as reflected here by changes in theta band activity in the posterior parietal cortex, a central hub of the default-mode network, which embodies emotional and autobiographical memory functions.…”
Section: Discussionmentioning
confidence: 85%
“…However, Foster and Parvizi's (2012) contribution raises the suggestion that the low-frequency entrainment dynamics in the resting state may in part be defined by the characteristic idling rhythm inherent to different functional systems of the cortex (c.f. Groppe et al, 2013) as been for example seen with theta-gamma PAC within the hippocampus (Lisman and Jenson, 2013). Sensorimotor systems are classically defined as owning both ‘idling’ rhythms at both the Beta range (12–30 Hz) as well as the alpha ‘Mu’ range (8–12 Hz) (Mackay, 1997).…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, microstates have typically been regarded as broad-band phenomena. Microstates may thus take into account the broad range of frequency components observable in the human brain (Groppe et al, 2013). Furthermore, the typical features extracted from microstate analyses, such as mean durations and percentages of time covered, are independent of signal amplitudes.…”
Section: Eeg Microstates and Oscillatory Brain Statesmentioning
confidence: 99%